2017
DOI: 10.1089/lrb.2017.0017
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Aqua-Lymphatic Therapy on Lower Extremity Lymphedema: A Randomized Controlled Study

Abstract: ALT was found to be a safe effective method for unilateral lower extremity lymphedema patients during the maintenance phase of Complex Decongestive Physiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…The results of our study support the prior findings [11][12][13][14] that a water program has positive effects not only for lymphedema reduction, improving psychoemotional state of women after surgical treatment, but also can lead to significant impact on vital capacity, forced vital capacity, forced expiratory volume in one second, maximal voluntary ventilation, inspiratory reserve volume, expiratory reserve volume.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of our study support the prior findings [11][12][13][14] that a water program has positive effects not only for lymphedema reduction, improving psychoemotional state of women after surgical treatment, but also can lead to significant impact on vital capacity, forced vital capacity, forced expiratory volume in one second, maximal voluntary ventilation, inspiratory reserve volume, expiratory reserve volume.…”
Section: Discussionsupporting
confidence: 90%
“…A review of several studies [1][2][3][4][5] show that breast cancer survivors have functional and radiological pulmonary changes, that require increased attention from the physical therapist. Some studies emphasize the importance of water therapy [12][13][14] and Pilates program [8,9] for improving cardiopulmonary fitness and overcoming upper extremity disorders in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed analysis of literary sources [4,9,10,13,23,24], including randomized clinical trials, pilot-analysis, and metaanalysis, showed that women after breast cancer treatment experienced radiotherapy-and chemotherapy-induced cardiovascular system adverse events, fatigue, and cardiotoxicity. Some papers considered aerobic physical activity [26] and water physical therapy [20,27,28] for pain and lymphedema reduction in post-mastectomy women, but they did not examine the effect of water exercises on the improvement of hemodynamic parameters in breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%